Do Invasive Earthworms Affect the Functional Traits of Native Plants? - Thouvenot, Lise; Ferlian, Olga; Beugnon, Rémy; Künne, Tom; Lochner, Alfred; Thakur, Madhav P.; Türke, Manfred; Eisenhauer, Nico (Frontiers in Plant Science, 2021)
As ecosystem engineers, invasive earthworms are one of the main drivers of plant community changes in North American forests previously devoid of earthworms. One explanation for these community changes is the effects of earthworms on the reproduction, recruitment, and development of plant species. However, few studies have investigated functional trait responses of native plants to earthworm invasion to explain the mechanisms underlying community changes. In a mesocosm (Ecotron) experiment, we set up a plant community composed of two herb and two grass species commonly found in northern North American forests under two earthworm treatments (presence vs. absence). We measured earthworm effects on above- and belowground plant biomass and functional traits after three months of experiment. Our results showed that earthworm presence did not significantly affect plant community biomass and cover. Furthermore, only four out of the fifteen above- and belowground traits measured were affected by earthworm presence. While some traits, such as the production of ramets, the carbon and nitrogen content of leaves, responded similarly between and within functional groups in the presence or absence of earthworms, we observed opposite responses for other traits, such as height, specific leaf area, and root length within some functional groups in the presence of earthworms. Plant trait responses were thus species-specific, although the two grass species showed a more pronounced response to earthworm presence with changes in their leaf traits than herb species. Overall, earthworms affected some functional traits related to resource uptake abilities of plants and thus could change plant competition outcomes over time, which could be an explanation of plant community changes observed in invaded ecosystems.